Review of Reconstructing the Variant Generation Process of Hadith: Based on the Quantitative and the Isnād- cum-Matn Analysis. By Hiroyuki Yanagihashi - Su, I-Wen (JAOS, 2024)
Reconstructing the Variant Generation Process of Hadith: Based on the Quantitative and the Isnād- cum-Matn Analysis. By Hiroyuki Yanagihashi. Sheffield, UK: eqUinox PUBlishinG, 2023. Pp. xiii + 287. $100, £75.